Innovations in green building contract and risk allocation: an analysis of the employer’s obligations - Mat Yaman, Khariyah; Abdul Ghadas, Zuhairah Ariff; Makhtar, Maheran (Springer, 2024)
Sustainability in construction hinges on harmonising with nature and is tightly interwoven with balancing economic and environmental interests. Concerted efforts from all stakeholders, especially the employer, are essential. The employer’s role is pivotal in setting a project direction within the construction supply chain. This paper explored the potential legal duties and obligations impacting employers pursuing sustainability in building construction projects. The research looked into the applicable sustainability requirements in buildings by applying descriptive analysis, content analysis, and analytical analysis approaches within the doctrinal legal research methodology parameter. The requirements were subsequently compared and evaluated within Malaysia’s existing framework of building standard forms. The analysis revealed that whilst the current structure of the standard forms affecting the employer’s obligations is to be maintained, there are augmented obligations on the employer’s part that must be addressed. These augmented obligations are classified into a framework or parameter of em-ployer’s obligations that can be introduced into the current structure of the building standard forms in Malaysia. The findings form part of the overall strategy to have a standard form catering to sustainable building projects in Malaysia. They are significant in providing a platform for understanding the sustainability requirements and legal duties and obligations that ensue on the employer’s part.